A single intraarticular injection of a tranexamic acid-modified hyaluronic acid (HA/TXA) alleviates pain and reduces OA development in a murine model of monosodium iodoacetate-induced osteoarthritis - Brochard, Sybille; Boumédiene, Karim; Mercier, Jéromine; Agin, Véronique; Conrozier, Thierry; Baugé, Catherine (Frontiers in Pharmacology, 2024)
Rationale: Tranexamic acid (TXA) is a strong and specific plasminogen activator inhibitor with inhibitory effects on the matrix metalloproteases involved in the pathophysiology of osteoarthritis (OA) through targeting of the fibrinolysis pathway. In this study, we evaluated the analgesic and chondroprotective effects of a HA-tranexamic acid (HA/TXA) conjugate, compared to HA alone and placebo, in an animal model of knee OA. Methods: Knee OA was induced in 15 C57bl/6J mice by IA injection of 0.75 mg of Monosodium IodoAcetate (MIA). At day 28, the mice received 1 IA injection of 10 µl of saline (control-group), or of HA or of HA/TXA. Tactile sensitivity was assessed using von Frey filaments. Stimulations started at 1 g and increased until a response was obtained (up to 4 g). A response to the stimulus was counted if the animal withdrew its paw. If the animal responded to the 1 g stimulation, stimulation was reduced until the lack of response was observed (up to 0.2g). At day 56, mice were euthanized for knee histological assessment. Cartilage degradation was assessed using the OARSI score. Statistical analysis was performed on GraphPad Prism 8.0.2 software. Kruskal-Wallis or Mann-Whitney tests were performed as appropriate. Results: Just before treatment administration, no intergroup difference in paw withdrawal threshold was observed. Throughout the experiment animals given saline and HA had a lower paw withdrawal threshold than those treated with HA/TXA (p<0.01). In the control group OARSI score was 5.5+0.6. In HA and HA+TXA treated mice the OARSI score was 3.2+0.8 and 3.1+0.5 (p<0.01) showing that both treatments were able to reduce OA progression. Conclusion: In this animal model of MIA induced KOA, a single IA injection of a HA/TXA conjugate resulted in a greater efficacy on pain than both saline and HA. HA and HA/TXA exhibited chondroprotective effects compared to placebo.